MANAGEMENT CLIMACTERIC AND MENOPAUSE, AFTER THE ACONTECLMLENTOS IN THE WOMEN'S HEALTH INITIATIVE - Pacheco Romero, José (2015)
In the beginning of 2003, the average life reaches about 70 years in Latin America and reaches 80 years in industrialized countries such as Japan, the percentage of people over 60 years for 2000 was in Peru 7 2%, by 2025 the proportion is estimated at 12.6% and by 2050 will triple to 22.4%. Therefore, the importance of reflecting on the management of menopause and menopause, especially after the events with the Women's Health Initiative (WHI). This paper reviews the events immediately preceding and following the WHI hormonal management in menopausal women or when, in July 2002, JAMA published the findings that had forced researchers to make the determination that it is known to all menopáusicas- including our patients. The author makes a brief reflection on the pros and cons of hormone therapy at menopause, who try and therapeutic possibilities for the symptoms associated with this time of life.